2010
DOI: 10.1021/bm100566j
|View full text |Cite
|
Sign up to set email alerts
|

Swelling, Mechanical, and Barrier Properties of Albedo-Based Films Prepared in the Presence of Phaseolin Cross-Linked or Not by Transglutaminase

Abstract: Edible films were obtained from Citrus paradisi grapefruit albedo homogenates and bean protein phaseolin modified or not by the enzyme transglutaminase. Swelling capability, barrier performance to water vapor, oxygen and carbon dioxide, and mechanical properties of such films were investigated. The addition of the protein, mostly in the presence of transglutaminase, provide films less swellable at pH values above 5 compared to films made by albedo homogenates only, whereas the action of the enzyme clearly impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Similar changes regarding the barrier properties were observed in thin film preparations of grapefruit albedo homogenates combined with the bean protein phaseolin after transglutaminase-catalyzed crosslinking. However, in contrast to the whey protein films studied by Di Pierro et al (2006), the transglutaminase-treated albedo homogenate–phaseolin films not only revealed higher tensile strength but also an approximately twofold increase in their elasticity (Mariniello et al 2010). …”
Section: Formation Of Protein Networkmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar changes regarding the barrier properties were observed in thin film preparations of grapefruit albedo homogenates combined with the bean protein phaseolin after transglutaminase-catalyzed crosslinking. However, in contrast to the whey protein films studied by Di Pierro et al (2006), the transglutaminase-treated albedo homogenate–phaseolin films not only revealed higher tensile strength but also an approximately twofold increase in their elasticity (Mariniello et al 2010). …”
Section: Formation Of Protein Networkmentioning
confidence: 91%
“…Edible thin films from various different proteins have been prepared by enzyme-catalyzed crosslinking with microbial transglutaminase (Di Pierro et al 2006; Mariniello et al 2010), and recently, also with tyrosinase and laccase (Juvonen et al 2011). For example, films containing transglutaminase-crosslinked whey proteins embedded in a chitosan matrix showed (1) low solubility in water (2) reduced permeability for oxygen, carbon dioxide, and water vapor, and (3) enhanced elongation to break but lower deformability than noncrosslinked films (Di Pierro et al 2006).…”
Section: Formation Of Protein Networkmentioning
confidence: 99%
“…Another interesting protein is phaseolin [255][256][257][258][259], a globular protein from Phaseulus Vulgaris L. and proteins purified from Vicia Ervilia. Many papers have been published recently using as crosslinking agent the enzyme transglutaminase, and as plasticizers glycerol or trehalose with or without different polysaccharides to obtain composite films.…”
Section: Emerging Proteins From Plant Kingdommentioning
confidence: 99%
“…Most of the biodegradable plastics are produced utilizing renewable biomass sources, whereas fossil-fuel plastics (poly-ethylene, -vi- invertebrates and vertebrates [39,41,42,49].…”
mentioning
confidence: 99%
“…It was demonstrated that the enzymecatalyzed formation of protein crosslinks into the film network gener-ally determines a decreased solubility of the bioplastics and increases its capacity to stretch. Concerning the pectin-based materials, the effect of mTG was shown both to significantly increase the barrier properties to both oxygen and carbon dioxide and to confer to these bioplastics a moderate permeability to water vapour [41,42]. These modifications of bioplastics characteristics suggest their possible use in a variety of situations, one of which could be the edible wrapping of high-moisture food to prevent their quality changes.…”
mentioning
confidence: 99%